Penerapan Arsitektur Islam terhadap Bentuk- Bentuk Simbol dan Ornamen pada Masjid di Kota Kendari - Muh Alfandi Nahminar; Rizky Dini Mentari; La Pande Jurumai (LP3M Universitas Muhammadiyah Kendari, 2022)
Islamic architecture is a building work of art that applies deep Islamic forms, ornaments, symbols and values ​​without hindering the use of modern building technology as a tool in expressing this essence. Islamic architecture is guided by the Al-Quran and Hadith. The characteristics of Islamic architecture are mosques. The mosque in the city of Kendari has many unique forms with symbols and ornaments on every mosque in the city of Kendari. From the uniqueness of mosques in the city of Kendari, the author will conduct research on the forms of symbols in mosques in the city of Kendari. This research method uses a qualitative method with a descriptive approach. This method is carried out by serving directly at every mosque in the city of Kendari. The results of this study indicate that the shape and location of the symbols and ornaments on each mosque in the city of Kendari are in accordance with Islamic architecture.